New records of two hyphomycetous fungi Monodictys putredinis (Wallr.) Hughes and Stachybotrys atra Corda for Bangladesh (Bangladesh Journal of Plant Taxonomy, 2010)
Not available.Keywords: Monodictys putredinis; new records; Stachybotrys atra.DOI: 10.3329/bjpt.v17i1.5397Bangladesh J. Plant Taxon. 17(1): 101-103, 2010 (June)